Effects of robotic rehabilitation on recovery of hand functions in acute stroke: A preliminary randomized controlled study - Karagözoğlu Coşkunsu, Dilber; Akçay, Sümeyye; Erkan Oğul, Özden; Akyol, D. Kübra; Öztürk, Necla; Zileli, Füsun; Baştan Tüzün, Birgül; Krespi, Yakup (Wiley, 2022)
Objective The aim of this study was to investigate the effects of EMG-driven robotic rehabilitation on hand motor functions and daily living activities of patients with acute ischemic stroke. Materials & Method A preliminary randomized-controlled, single-blind trial rectuited twenty-four patients with acute ischemic stroke (<1 month after cerebrovascular accident) and randomly allocated to experimental group (EG) and control group (CG). Neurophysiological rehabilitation program was performed to both EG and CG for 5 days a week and totally 15 sessions. The EG also received robotic rehabilitation with the EMG-driven exoskeleton hand robot (Hand of Hope (R), Rehab-Robotics Company) 15 sessions over 3 weeks. Hand motor functions (Fugl-Meyer Assessment-Upper Extremity (FMA-UE) and Action Research Arm Test (ARAT)), activities of daily living (Motor Activity Log (MAL)), force and EMG activities of extensor and flexor muscles for the cup test were evaluated before treatment (pretreatment) and after the 15th session (posttreatment). Results Eleven patients (59.91 +/- 14.20 yr) in the EG and 9 patients (70 +/- 14.06 yr) in the CG completed the study. EG did not provide a significant advantage compared with the CG in FMA-UE, ARAT and MAL scores and cup-force and EMG activities (p > .05 for all). Conclusion In this preliminary study, improvement in motor functions, daily living activities and force were found in both groups. However, addition of the EMG-driven robotic treatment to the neurophysiological rehabilitation program did not provide an additional benefit to the clinical outcomes in 3 weeks in acute stroke patients.
Keywords: Hand; Rehabilitation; Robotics; Stroke Acute